2001
DOI: 10.1111/j.1365-2621.2001.tb15201.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Physicochemical Properties and Hydration Behavior of Oat Gum and Oatrim in Meat‐based Patties

Abstract: Goat/rabbit meat patties were formulated using oatrim (0.5, 1.0, 2.0, %) and oat gum (0.5, 1.0, and 2%). Patties were evaluated for sensory attributes, nutrient content and hydration behavior. Moisture content decreased with increased oatrim and oat gum addition. Protein content of patties containing 2% oatrim slightly increased. However, ash values were lower than control. Shear force values were higher for oatrim containing patties than for oat gum. Patties containing oatrim and oat gum received favorable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
2
14
1
1
Order By: Relevance
“…Such decreases were greater in the hydrated oatmeal-amended sausage than in all types of meat sausages. These results are consistent with previous reports that the addition of oat bran, soy protein, or starch improves the textural properties by decreasing product hardness (Pszczola, 1991;Dawkins et al, (2001). Desmond and Troy (1998) reported that beef burgers containing oat fiber have decreased hardness values when compared to the low-fat control.…”
Section: Tpasupporting
confidence: 83%
“…Such decreases were greater in the hydrated oatmeal-amended sausage than in all types of meat sausages. These results are consistent with previous reports that the addition of oat bran, soy protein, or starch improves the textural properties by decreasing product hardness (Pszczola, 1991;Dawkins et al, (2001). Desmond and Troy (1998) reported that beef burgers containing oat fiber have decreased hardness values when compared to the low-fat control.…”
Section: Tpasupporting
confidence: 83%
“…They attributed the fall to decreased binding within meat matrix due to lower protein in bran patties as protein in general tend to exhibit good binding capacity. Dawkins et al (2001) also observed that the shear press value tends to decrease with higher levels of oatrim and oat gum.…”
Section: Fiber and Tendernessmentioning
confidence: 77%
“…The sensory panel showed no significant difference for tenderness, juiciness, beef flavor intensity and overall palatability at the different added fiber levels. Juiciness of oat gum and oatrim based meat patties was slightly higher than that of control patties (Dawkins et al, 2001). Tenderness was slightly higher for oat gum than oatrim patties, regardless of meat used.…”
Section: Fiber and Organoleptic Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…They show some functional properties, such as WHC and FBC, due to the porous structure formed by polysaccharides, which can hold water through hydrogen bonds (Dawkins et al, 2001). Cereal fibers have more insoluble dietary fiber (IDF), whereas fibers from fruit and vegetables have a high amount of soluble dietary fiber (SDF).…”
Section: Dietary Fibermentioning
confidence: 99%